The Lived experiences of the nursing faculty and students of Saint Paul University with problem based learning - Marallag, Alida L. (2002)
The study focused on the experiences surrounding Problem-Based Learning (PBL) in St. Paul University as perceived by the nursing faculty and students, as part of the 10-year re-engineering of the Bachelor of Science in Nursing program. It aimed to 1) determine the lived experiences of the Nursing faculty and students, 2) identify the similarities and differences in the experiences, and 3) define the meanings faculty and students make out of their experience by describing the phenomena related to those experiences. The study made use of a phenomenological approach with qualitative triangulation of observation, administration of questionnaires and interviews to obtain and extract data. Non-participant observation procedures were carried out to describe the PBL process in St. Paul University-College of Nursing. Administration of questionnaires provided initial subjective data from respondents and responses were categorized based on the common patterns that emerged and provided basis for questions used in the PBL life stories. The explication of the respondents' life stories obtained through focus group discussions and personal interviews involving guided conversation, provided deeper understanding of the experiences with meaning extracted and constructed by the latter. The data were categorized based on emerging patterns and themes using the constant comparative method of qualitative data analysis. The PBL process employed by the College of Nursing involved the presentation of prototype nursing and other related problems to students as stimuli and starting points for learning and discussion. The problems were identified, analyzed, synthesized and resolved by 8-10 students working in groups facilitated by their respective tutors utilizing small group learning/discussions, engaging in self-directed/independent study and tutorial sessions iteratively. Three major themes were extracted and described the experience. These were referred as 1) transition PBL, 2) going through PBL, and 3) gains in PBL. Basically, the cycle involves a process of change or transition beginning with strong feelings of rejection, doubt and fear coupled with initial coping and adjustment. What followed was a more positive way of coping, getting through things and facing challenges to fit into the system and finally, an acceptance of the change which enabled them to develop insights, make meaningful learning out of the experience and integrate learning to everyday tasks. In general, the findings revealed that the PBL experience was stressful and difficult but worthwhile as well. The findings in the study indicated that stress accompanies curriculum transition and change. It required adjustments and the process was fraught with difficulties. Findings on the implementation issues and PBL outcomes described in previous researches were supported in this study. There was evidence to suggest that the use of problem cases and engaging students in small group activities and independent study, led to the development of responsibility to learn one's own and skills to work in groups. Faculty and students were likely to shift their attitudes in a positive direction towards change once they have direct experience and when the change is perceived to have benefits that outweigh the difficulties, as in the respondents' PBL experience. Lastly, in order for curriculum innovation to be sustained, continuing faculty education and training are needed as well as establishing new social and learning contracts with students.
Major project (Master in Health Professions Education)--University of the Philippines Manila
Keywords: Problem-based learning